Diagnosis and Surgical Management of Nonsyndromic Nine Supernumerary Teeth and Leong's Tubercle - Cruz, Christiane V. (Case Rep Dent, 2016)
Nonsyndromic multiple supernumerary teeth (ST) and Leong's tubercle are a condition with a very low prevalence and a multidisciplinary approach is required to restore function and aesthetics. So, this case report aimed at presenting a rare case of nonsyndromic nine supernumerary teeth and Leong's tubercle in a pediatric patient, without any evident familial history, showing its diagnosis and surgical management.